Unveiling Vocabulary Learning Strategies: A Mixed Methods Study among EAP Students - فرزانه اکبری; فرحناز ریمنی نیکو; شیما احمدی آزاد (Journal of Applied Linguistics)
This study focused on the importance of Vocabulary Learning Strategies (VLSs) in English for Academic Purposes (EAP) and how Iranian EAP students learn academic vocabulary. The study used a predominantly quantitative approach by gathering data from 238 participants through online self-report VLS questionnaires, which were analyzed using SPSS-26. A triangulation approach was used to ensure accuracy and consistency, with qualitative data gathered through semi-structured interviews with 20 students. The analysis revealed that participants frequently used strategies for incorporating new vocabulary into their repertoire. Additionally, teacher-related, student-related, and material-related themes emerged through coding the participants’ beliefs. The results indicated that raising learners’ consciousness of VLSs, training teachers, providing tasks for all language skills, using technology, materials revision, and developing autonomous and independent learning can help with vocabulary acquisition and the satisfaction of EAP students. Overall, this study highlights the importance of VLSs in EAP and provides insights into effective strategies for acquiring academic vocabulary.